Left Brachiocephalic Vessel Venous Tumor Thrombus in a Laryngeal Cancer Patient Detected with PET-CT Imaging - Pelin Ozcan Kara; Zehra Pinar Koc; Mesut Sabri Tezer; Taylan Kara (Journal of Otolaryngology Advances, 2017)
Accurate diagnosis of tumor thrombus and distinguishing benign thrombus from tumor thrombus avoid unnecessary anticoagulant treatment of oncological patients and it is important for patient management. In this case report, the role of FDG PET/CT in the presentation of a suspicious tumor thrombus in the left brachiocephalic vein of a patient with known laryngeal carcinoma and leiomyosarcoma diagnosis is presented.
Keywords: Laringeal cancer